Estimating policy pressure for China's cultivated land use protection based on an extended index. (October 2017) - Chen, Jiandong; Cheng, Shulei; Song, Malin
Abstract: Based on existing references, using the decomposition technique of the second model of the logarithmic mean Divisia index (LMDI) decomposition method and the principle of "jointly created and equally distributed" of the Refined Laspeyres (RL) index, this paper developed a new policy pressure index and applied it to estimate the policy pressure for China's cultivated land use protection. The results indicated that, first, the policy pressure for China's cultivated land use protection experienced an inverted U–shaped evolution from 1997 to 2014 and that the status of cultivated land use protection policy pressure in each province was related mainly to local economic development and industrial structure. Second, agricultural production efficiency and industrial structure exerted positive influences on policy pressure for cultivated land use protection, but economic scale exerted negative influences on it. Third, the differences among areas with different policy pressures were explained mainly by two factors: the economic scale and agricultural production efficiency. The former exerted a positive and the latter a negative influence. Highlights: A policy pressure index is developed. The second model of the LMDI decomposition technique is chosen to decompose the index by factor. The index is decomposed by group on the principle of jointly created and equally distributed. Policy pressure for cultivated land use protection in China is estimated and decomposed.